Assessment as Learning: How Does Peer Assessment Function in Students' Learning? - Yin, Shengkai; Chen, Fang; Chang, Hui (Frontiers in Psychology, 2022)
Peer assessment is employed as one fundamental practice of classroom-based assessment in terms of its learning-oriented and formative nature. The exercise of peer assessment has multiple and additional benefits for student learning. However, research into the learning processes in peer assessment is scarce both in theory and in practice, making it difficult to evaluate and pinpoint its value as a tool in assessment as learning (AaL). This paper focuses both on the learning process and outcome through assessment activities. We set out with three specific aims in mind: (1) to examine students’ assessment performance in context, (2) to evaluate its impact on student progress, and (3) to illuminate teachers on organizing assessment activities. 29 undergraduate students were required to award scores twice in one semester on two argumentative speaking tasks to their peers and to themselves. Many-facet Rasch model (MFRM) analysis was conducted to measure the rater effects both at the group level and the individual level. Bias/interaction analysis was performed to diagnose the relationship between different facets, and score variations between sessions were compared. Questionnaire and semi-structured interview data were also collected to explore factors and strategies that could interfere with the AaL outcome. Findings indicated that students made progress in the delivery, organization and language use in argumentative speaking by self-regulation with the assistance of metacognitive and cognitive strategies. This paper validated both the feasibility and the effectiveness of peer assessment for student learning. Guidelines for implementation of PA as AaL are provided.